PENGARUH VIDEO PENDIDIKAN KESEHATAN TENTANG KEPERAWATAN PENYAKIT HIPERTENSI PADA STAFF TENAGA KEPENDIDIKAN - Fajar Agung Nugroho; Cahyu Septiwi; Dewi Purbaningrum Vellayudhan (STIKES Pemkab Purworejo, 2023)
Background: The World Health Organization (WHO) revealed that, in 2021, it was estimated that there would be 1.28 billion adults. In the same year, 3,834 cases of hypertension were recorded. In order to disseminate sufficient knowledge to the public about preventing hypertension, this information can be conveyed through various types of media, namely videos and health education. Objective: To determine the effect of health education videos about hypertension on educational staff. Method: pre-experimental, specifically a one-group pretest-posttest design. The population consists of 33 educational staff members. The instrument used to measure knowledge utilizes the HFQ (Hypertension Fact Questionnaire). Results: The study revealed a significant influence of videos and leaflets on respondents' knowledge, with a p-value of 0.000. The average knowledge value before the intervention (pretest) was 56.97, and after the intervention (posttest), it increased to 87.58. The research results demonstrated a significant impact of videos and leaflets on respondents' knowledge, with a p-value of 0.000. Conclusion: There is a noteworthy influence of health education videos about hypertension on educational staff.